2007
DOI: 10.1177/0969733007075868
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Conscience in Relation To Stress of Conscience

Abstract: Every day situations arising in health care contain ethical issues influencing care providers' conscience. How and to what extent conscience is influenced may differ according to how conscience is perceived. This study aimed to explore the relationship between perceptions of conscience and stress of conscience among care providers working in municipal housing for elderly people. A total of 166 care providers were approached, of which 146 (50 registered nurses and 96 nurses' aides/enrolled nurses) completed a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
101
0
11

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(115 citation statements)
references
References 39 publications
(18 reference statements)
3
101
0
11
Order By: Relevance
“…Nurses today, more than ever, are facing challenging situations which requires difficult ethical decisions regarding patients care. One of the factors affecting the nursing responses to these ethically difficult situations is conscience (Juthberg et al, 2007). It is so important for the nurse to discuss about the meaning of conscience.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses today, more than ever, are facing challenging situations which requires difficult ethical decisions regarding patients care. One of the factors affecting the nursing responses to these ethically difficult situations is conscience (Juthberg et al, 2007). It is so important for the nurse to discuss about the meaning of conscience.…”
Section: Introductionmentioning
confidence: 99%
“…El concepto de estrés de conciencia consta de dos dimensiones : 1) las demandas internas : aquellas que le permiten al personal de enfermería mantener su identidad como profesionales buenos de la salud, y 2) la dimensión de demandas externas la cual se define como la consecuencia de la obligación del enfermero de proporcionar cuidados que le hacen sentir mal, lo anterior puede ocurrir cuando el individuo busca la aprobación de los demás y teme a la desaprobación , lo que puede generar sentimientos de culpa lo cual puede derivar en conflictos de conciencia ( Juthberg , Eriksson , Norberg & Sundin, 2007).El estrés de conciencia tiene consecuencias que pueden afectar la salud y el bienestar en los proveedores de la salud lo que a su vez compromete la misma calidad del cuidado, convirtiendo esta problemática en un círculo vicioso (Juthenberg, 2010). …”
Section: Los Centros De Integración Juvenil (Cij 2012) Enunclassified
“…Nurses indicate that stress of conscience is attributed to factors such as deficient social support from superiors SHORTENED TITLE HERE IN ALL CAPS 8 and low levels of resilience (Glasberg et al, 2006;Juthberg, Eriksson, Norberg, &Sundin, 2007;McHale, 2009). …”
Section: Stress Of Conscience In Healthcarementioning
confidence: 99%
“…Empirical studies have shown that healthcare personnel sometimes refer to conscience when talking about being in ethically-difficult everyday care situations. A study conducted by Juthberg et al (2007) examined the relationship between conscience and burnout among careproviders in elder care, exploring the relationship between stress of conscience and burnout, and between perceptions of conscience and burnout. A questionnaire was distributed in municipal housing for older people to 166 care providers, 146 of which (50 registered nurses and 96 nurses' aides/enrolled nurses) participated.…”
Section: Stress Of Conscience In Healthcarementioning
confidence: 99%